Lexical-semantic classification of euphemisms of the feminine gender in the Uzbek language: Klasifikasi leksikal-semantik dari eufemisme jenis kelamin feminin dalam bahasa Uzbek - Gulnamova Shakhnoza Kakhramonovna; B. Mengliyev (Universitas Muhammadiyah Sidoarjo, 2019)
The two sexes - men and women - are not only biologically diverse, but also have their differences in language use. This article presents a lexical-semantic classification of euphemisms of female sexuality in Uzbek, and analyzes each of the euphemic agents in each group.